2006
DOI: 10.1002/bjs.5186
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effectiveness of antibiotic prophylaxis in prevention of wound infection after mesh repair of abdominal wall hernia

Abstract: Antibiotic prophylaxis did not prevent the occurrence of wound infection after groin hernia surgery. More trials are needed for complete evidence in other areas of abdominal wall hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 28 publications
5
50
0
4
Order By: Relevance
“…Also the percentage of wound infection in the placebo group has a large variation between 0 and 15 %; to correct for this broad baseline percentage of wound infections we propose to enlarge the confidence interval from 95 to 99 % for the overall analysis. The same methods were followed as described in one of the earlier published meta-analyses [48]. The results of the analysis of data from all 12 RCTs demonstrate an incidence of wound infection of 82/1,862 (4.4 %) patients in the placebo group and 48/1,831 (2.6 %) after antibiotic prophylaxis.…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…Also the percentage of wound infection in the placebo group has a large variation between 0 and 15 %; to correct for this broad baseline percentage of wound infections we propose to enlarge the confidence interval from 95 to 99 % for the overall analysis. The same methods were followed as described in one of the earlier published meta-analyses [48]. The results of the analysis of data from all 12 RCTs demonstrate an incidence of wound infection of 82/1,862 (4.4 %) patients in the placebo group and 48/1,831 (2.6 %) after antibiotic prophylaxis.…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…1), since they are of a possibly lower quality because of their methods of randomisation but including or excluding them in the analysis does not influence the overall conclusions. Since a formal presentation of the data used together with a systematic review is beyond the scope of this commentary, I want to point out that the same methods were follow as described in one of the earlier published meta-analysis [8].…”
Section: The Current Evidence Based Verdict On Antibiotic Prophylaxismentioning
confidence: 99%
“…A Cochrane meta-analysis on this topic in 2004 concluded that antibiotic prophylaxis in mesh repair of inguinal hernias can neither be recommended nor discarded. 5 Hence, we designed this study to define the role of prophylactic antibiotics in prevention of wound infection in mesh inguinal hernia repair and to analyse the risk factors for wound infection in mesh inguinal hernia repair.…”
Section: Introductionmentioning
confidence: 99%